2016
DOI: 10.1159/000445434
|View full text |Cite
|
Sign up to set email alerts
|

Associations of TNFα <b><i>-308G>A</i></b>, TNFα <b><i>-238G>A</i></b>,<b> </b>IL-1α <b><i>-889C>T</i></b> and IL-10 <b><i>-1082G>A </i></b>Genetic Polymorphisms with Atopic Diseases: Asthma, Rhinitis and Dermatitis

Abstract: Background: Polymorphisms of cytokine genes are an interesting focus for association studies involving atopic diseases due to their role in immune cell communications during inflammation. The aim of this study was to investigate associations of TNFα -308G>A, TNFα -238G>A, IL-1α -889C>T and IL-10 -1082G>A polymorphisms with atopic diseases with adjustment for confounding lifestyle and environmental factors. Methods: This study was performed on 356 Croatian students. The diagnosis of atopic asthma, atopic rhinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 69 publications
(95 reference statements)
0
4
0
1
Order By: Relevance
“…The disease is the effect of genetic and environmental influences [4] as well as interactions between immunological factors and skin barrier defect [5,6] .…”
mentioning
confidence: 99%
“…The disease is the effect of genetic and environmental influences [4] as well as interactions between immunological factors and skin barrier defect [5,6] .…”
mentioning
confidence: 99%
“…In 2013, Chen, et al included seven case-control studies [17–19, 21, 32, 34, 35] to perform a meta-analysis of the association between the IL-10 -1082 A/G polymorphism and the risk of atopic dermatitis [23]. In the present study, we collected the available data from diverse sources and finally added another eight new case-control studies [15, 16, 20, 30, 31, 33, 36, 37] to conduct another updated meta-analysis under the genetic models of allele A vs. G, GG vs. AA, AG vs AA, AG + GG vs AA, GG vs AA+AG and carrier A vs. G. Subgroup analyses stratified by ethnicity, country and HWE were also conducted. Our data failed to support the strong genetic link between the IL-10 -1082 A/G SNP and the risk of atopic dermatitis, which is in line with the outcomes of the above meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the genotypic distribution of control groups in some studies was not in line with the Hardy-Weinberg equilibrium. Fourth, of the eligible case-control studies, only allelic frequency data were extracted in one study [21], and the combined genotypic frequency (AG + GG) of the IL-10 -1082 A/G polymorphism was obtained in another study [31]. Fifth, even though we obtained haplotypic data for the − 1082 A/G, − 819 T/C, − 592 A/C polymorphisms within the IL-10 genes, including “ACC”, “ATA”, and “GCC”, very limited data resulted in the failure of related meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…35 However, GA genotype of TNF-α (308 G/A) is significantly decreased and the frequency of GG genotype is increased in the patients showing a negative association of this polymorphism with AD and atopic asthma in Iranian 23 and Croatian patients. 36 On the contrary, some studies have indicated no association of TNF-α (308 G/A) polymorphism with AD susceptibility in English, 37 German, 20 Americans. 14 Chinese, 38 and Macedonians subjects.…”
Section: Discussionmentioning
confidence: 99%